Selective breeding for physical inactivity produces cognitive deficits via altered hippocampal mitochondrial and synaptic function - Kerr, Nathan R.; Kelty, Taylor J.; Mao, Xuansong; Childs, Thomas E.; Kline, David D.; Rector, R. Scott; Booth, Frank W. (Frontiers in Aging Neuroscience, 2023)
Physical inactivity is the 4th leading cause of death globally and has been shown to significantly increase the risk for developing Alzheimer’s Disease (AD). Recent work has demonstrated that exercise prior to breeding produces heritable benefits to the brains of offspring, suggesting that the physical activity status of previous generations could play an important role in one’s brain health and their subsequent risk for neurodegenerative diseases. Thus, our study aimed to test the hypothesis that selective breeding for physical inactivity, or for high physical activity, preference produces heritable deficits and enhancements to brain health, respectively. To evaluate this hypothesis, male and female sedentary Low Voluntary Runners (LVR), wild type (WT), and High Voluntary Runner (HVR) rats underwent cognitive behavioral testing, analysis of hippocampal neurogenesis and mitochondrial respiration, and molecular analysis of the dentate gyrus. These analyses revealed that selecting for physical inactivity preference has produced major detriments to cognition, brain mitochondrial respiration, and neurogenesis in female LVR while female HVR display enhancements in brain glucose metabolism and hippocampal size. On the contrary, male LVR and HVR showed very few differences in these parameters relative to WT. Overall, we provide evidence that selective breeding for physical inactivity has a heritable and detrimental effect on brain health and that the female brain appears to be more susceptible to these effects. This emphasizes the importance of remaining physically active as chronic intergenerational physical inactivity likely increases susceptibility to neurodegenerative diseases for both the inactive individual and their offspring.